PENDEKATAN PDCA DALAM KEGIATAN PEMANTAUAN PENGENDALIAN MUTU DI LEMBAGA KURSUS DAN PELATIHAN - Riyantini, Riyantini (JIV-Jurnal Ilmiah Visi, 2017)
By having a challenge to escalate quality at course and training institutions (LKP) which is appropriate to 8 National Education Standards, it is necessary to have an approach related to management functions; planning, implementation, evaluation and improvement on institution management related to quality. Due to that reason, Plan Do Check and Act (PDCA) approach is implemented toward course and training institutions. Problem statement proposed is in what ways Plan Do Check and Act (PDCA) approach can escalate effectiveness in supervising the quality control at course and training institutions. The objective is to describe the implementation of PDCA approach at the institutions. The method used is a qualitative descriptive approach by conducting data observation to collect the data, interviews, and some related literature. PDCA approach which is useful for supervisors, can be used as work patterns, to implement quality changes, measure them, and improve the quality sustainably. Activities run by supervisors as quality controllers are making a commitment together with managers, planning, implementing, and assessing. This PDCA approach can escalate supervision effectiveness in controlling quality of course and training institutions.